Revitalisasi Taman Kanak-Kanak untuk Mendorong Pendidikan Anak Usia Dini di Daerah Pedesaan - Fatika Puteri Rosyi Prabowo; Puput Mulyono (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The purpose of this community service is focused on the revitalization of kindergartens in rural areas as an effort to stimulate public interest in early childhood education. This upgraded kindergarten is believed to be able to increase students' motivation and interest in learning. The method used in this study is based on a descriptive approach to identify problems in the target area. Data was collected using qualitative methods including interviews and field observations. The data was then analyzed to be used as a basis for decision making and choosing the right actions to address the problem. Practical application, kindergarten revitalization plays a major role in children's learning experiences. These spaces provide comfortable outdoor activities and act as learning stimuli for children to gain knowledge about nature. Furthermore, attractive landscapes can encourage people to enroll their children in early childhood education. The conclusion of this community service aims to revitalize kindergartens to create comfortable outdoor spaces and act as learning aids for students. This service has succeeded in providing a better landscape for kindergartens that contributes to a broader student learning experience. A more attractive view gives the school a new look to attract public interest in early childhood education.